Tandem differential mobility analysis-mass spectrometry reveals partial gas-phase collapse of the GroEL complex. - Hogan, C; Ruotolo, B; Robinson, C; Fernandez de la Mora, J (2011)
A parallel-plate differential mobility analyzer and a time-of-flight mass spectrometer (DMA-MS) are used in series to measure true mobility in dry atmospheric pressure air for mass-resolved electrosprayed GroEL tetradecamers (14-mers; ~800 kDa). Narrow mobility peaks are found (2.6-2.9% fwhm); hence, precise mobilities can be obtained for these ions without collisional activation, just following their generation by electrospray ionization. In contrast to previous studies, two conformers are found with mobilities (Z) differing by ~5% at charge state z ~ 79. By extrapolating to small z, a common mobility/charge ratio Z(0)/z = 0.0117 cm(2) V(-1) s(-1) is found for both conformers. When interpreted as if the GroEL ion surface were smooth and the gas molecule-protein collisions were perfectly elastic and specular, this mobility yields an experimental collision cross section, Ω, 11% smaller than in an earlier measurement, and close to the cross section, A(C,crystal), expected for the crystal structure (determined by a geometric approximation). However, the similarity between Ω and A(C,crystal) does not imply a coincidence between the native and gas-phase structures. The nonideal nature of protein-gas molecule collisions introduces a drag enhancement factor, ξ = 1.36, with which the true cross section A(C) is related to Ω via A(C) = Ω/ξ. Therefore, A(C) for GroEL 14-mer ions determined by DMA measurements is 0.69A(C,crystal). The factor 1.36 used here is based on the experimental Stokes-Millikan equation, as well as on prior and new numerical modeling accounting for multiple scattering events via exact hard-sphere scattering calculations. Therefore, we conclude that the gas-phase structure of the GroEL complex as electrosprayed is substantially more compact than the corresponding X-ray crystal structure.